A HElium NanoDroplet Isolation (HENDI) investigation of the weak hydrogen bonding in the propyne dimer (CH3CCH)2. Issue 45 (8th November 2018) - Gutiérrez-Quintanilla, A.; Briant, M.; Mengesha, E.; Gaveau, M.-A.; Mestdagh, J.-M.; Soep, B.; Crépin, C.; Poisson, L.
Abstract : A HElium Nanodroplet Isolation (HENDI) experiment was performed to explore the absorption spectra of the propyne monomer (CH3 CCH), dimer and (CH3 CCH)≥3 multimers in the vicinity of the CH stretch region ν 1 of the monomer. Abstract : A HElium Nanodroplet Isolation (HENDI) experiment was performed to explore the absorption spectra of the propyne monomer (CH3 CCH), dimer and (CH3 CCH)≥3 multimers in the vicinity of the CH stretch region ν 1 of the monomer. Ab initio calculations were performed at the MP2 level to document the potential energy surface of the dimer. This provided the necessary parameters to simulate the absorption spectrum of the dimer and thus facilitate the interpretation of the experiment. The central result was to observe three isomers of the dimer, hence reflecting the complexity of the weak CH⋯π H-bonding when several H-donors are at play.